Analysis of the Impact of Advanced Technologies on Business Processes - Krhač Andrašec, Eva; Medved, Tilen; Kern, Tomaž (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
This study examines how advanced manufacturing technologies influence the performance of business processes through a Business Process Management approach. A basic product manufacturing process was selected as a case study and modelled in its current (AS-IS) and redesigned (TO-BE) states using the EPC method in the ARIS tool. The redesigned process integrates 3D scanning, CAD modelling, additive manufacturing, and collaborative robotic assembly while removing manual fabrication, paper documentation, and repetitive handling activities. Both process models were compared using performance indicators, including the number of activities, documents, and the share of IT-supported tasks. A comparative analysis shows that technology integration allows mass customization and increases digital support and automation. The findings suggest that although advanced technologies enable long-term process standardization and data transparency, organizations may experience short-term structural complexity and implementation challenges. The study contributes empirical insight into how advanced technologies reshape process structure and performance measurement.